2002
DOI: 10.1097/00007890-200205270-00022
|View full text |Cite
|
Sign up to set email alerts
|

Indo-Asian experience of renal transplantation in Yorkshire

Abstract: Asian patients gained access to the transplant waiting list at a similar rate to the non-Asian white majority. Because of difficulties with HLA matching, Asian patients were significantly disadvantaged in receiving a transplant once listed, and there was a trend towards reduced posttransplant survival. Cadaveric donation was uncommon from within the Asian community; the reasons for which are likely to be complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
2
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 14 publications
1
24
2
1
Order By: Relevance
“…Higgins et al reported a nonactuarial graft survival of 73% and 72% at 3 years for South Asian and European patients, respectively, in Coventry and Warwickshire (16). In a recent article, however, Jeffrey et al suggested that South Asians suffer higher death rates with functioning grafts, and as a consequence they enjoy a lower transplant survival (58% at 5 years compared with 71% for non-Asians) (9). Death with a functioning graft at 5 years affected 11% of the non-Asians and 22% of the South Asians (PϽ0.03) in their cohort.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Higgins et al reported a nonactuarial graft survival of 73% and 72% at 3 years for South Asian and European patients, respectively, in Coventry and Warwickshire (16). In a recent article, however, Jeffrey et al suggested that South Asians suffer higher death rates with functioning grafts, and as a consequence they enjoy a lower transplant survival (58% at 5 years compared with 71% for non-Asians) (9). Death with a functioning graft at 5 years affected 11% of the non-Asians and 22% of the South Asians (PϽ0.03) in their cohort.…”
Section: Discussionmentioning
confidence: 96%
“…In transplantation, the experience of South Asians in the United Kingdom is often compared with that of African Americans in the United States, in that both groups suffer low rates of transplantation and have been reported to have poorer outcomes than their white counterparts (8,9). Jeffrey et al analyzed the outcomes of 608 transplant patients (52 South Asians) who underwent transplantation between 1985 and 1994.…”
mentioning
confidence: 99%
“…Three small UK studies appear to draw contradictory conclusions. Jeffrey et al, comparing the graft outcomes of 52 Indo-Asian transplant recipients with those of 556 non-Indo-Asians, reported a trend toward lower 5-year graft survival and a higher incidence of death with a functioning graft (6). However, Loucaidou et al, comparing 53 Indo-Asian transplant recipients with 192 non-Indo-Asians, (7) and Higgins et al, comparing 19 Indo-Asian transplant recipients with 157 non-Indo-Asians, (8) both found no differences in outcome, although even Loucaidou et al noted a tendency to worse 3-5 year survival in Indo-Asians, (which was not statistically significant).…”
Section: Introductionmentioning
confidence: 99%
“…This means that unless the Asian community donates organs in proportion to its need the waiting list situation will deteriorate even further (Ready 1988). But to date the UK South Asian community has an especially low rate of organ donation from deceased donors (DH 2008b;Jeffrey et al 2002). The South Asian population constitutes 4% of the UK population (ONS 2003), but over the last 6 years on average only 1.5% of those joining the Organ Donor Register and only 1.3% of deceased organ donors are South Asian (NHSBT 2008).…”
Section: Introductionmentioning
confidence: 99%